Karakteristik Ekstrak Alga Coklat (Sargassum polycystum) sebagai Antioksidan pada Perlakuan Perbandingan Pelarut Aseton dan Etilasetat - Santiyoga, I Komang Wiria; Suhendra, Lutfi; Wartini, Ni Made (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI; Vol 8 No 1 (2020): Maret, 2020)
Sargassum polycystum is one type of brown algae from Indonesia that is potentially a natural dye and antioxidants. The purpose of this study was to determine the effect of the comparison of acetone and ethyl acetate solvents on the characteristics of Sargassum polycystum extract as an antioxidant and determine the best ratio of acetone and ethyl acetate to produce the characteristics of Sargassum polycystum extract as an antioxidant. This experiment was designed using a simple randomized block design with a comparative treatment of acetone and ethyl acetate. The treatment comprised of eight levels: 1 : 0; 0.81 : 0.19; 0.67 : 0.33; 0.52 : 0.48; 0.38 : 0.62; 0.24 : 0.76; 0.1 : 0.9 and 0 : 1. The treatment is grouped into 2 groups based on the time of implementation. The data were analyzed by analysis of variance using minitab software 17 and be continued using the method of significantly different honest. The results of the showed that the comparison of the acetone and ethyl acetate solvents has a very significant effect on yield, fukosantin compounds, antioxidant activity, brightness level (L *), redness level (a *) and yellowish level (b *) in brown algae extract (Sargassum polycystum). Comparative treatment of acetone and ethyl acetate (1: 0) with dielectric constant 20.70 is the best treatment to produce brown algae extract (Sargassum polycystum) with a yield characteristic of 2.83 ± 0.42 percent, the content of the compound fukosantin 0.031 ± 0.005 g fukosantin/g, IC 50 163.43 ± 3.26 ppm, brightness level (L *) 19.60 ± 0.00, redness level (a *) 11.84 ± 0.01, yellowish level (b *) 8.83 ± 0.02. Keywords: Sargassum polycystum, fucosantin, antioxidant, acetone and ethyl acetate.